2021
DOI: 10.3390/ijms22179604
|View full text |Cite
|
Sign up to set email alerts
|

The Transcriptional Landscape and Hub Genes Associated with Physiological Responses to Drought Stress in Pinus tabuliformis

Abstract: Drought stress has an extensive impact on regulating various physiological, metabolic, and molecular responses. In the present study, the Pinus tabuliformis transcriptome was studied to evaluate the drought-responsive genes using RNA- Sequencing approache. The results depicted that photosynthetic rate and H2O conductance started to decline under drought but recovered 24 h after re-watering; however, the intercellular CO2 concentration (Ci) increased with the onset of drought. We identified 84 drought-responsiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…All four abiotic stress-induced TFs show a similar response profile to these stress conditions; however, compared with other ASIGs, PtNAC3 showed a more sensitive and vigorous expression response, indicating that it probably acts as a core transcription activator in abiotic stress response. The result showed that PtNAC3 was up-regulated under 4°C, 10°C, 30°C, 40°C temperatures compared with 20°C, and induced by 8 days of moderate drought treatment and slightly up-regulated for 23 days of progressive drought treatment, while its expression level was recovered to control level after rewatering one day [ 16 ]. We found that the response of these genes should be a very rapid process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All four abiotic stress-induced TFs show a similar response profile to these stress conditions; however, compared with other ASIGs, PtNAC3 showed a more sensitive and vigorous expression response, indicating that it probably acts as a core transcription activator in abiotic stress response. The result showed that PtNAC3 was up-regulated under 4°C, 10°C, 30°C, 40°C temperatures compared with 20°C, and induced by 8 days of moderate drought treatment and slightly up-regulated for 23 days of progressive drought treatment, while its expression level was recovered to control level after rewatering one day [ 16 ]. We found that the response of these genes should be a very rapid process.…”
Section: Resultsmentioning
confidence: 99%
“…For temperature treatment, two-month-old P. tabuliformis seedlings were transformed to a 4°C, 10°C, 20°C, 30°C, and 40°C climate chamber for 8 hours during the light. Drought treatment raw data was from Tariq Pervaiz's study [ 16 ]; each treatment mentioned above has six repeats. For salt and osmotic treatment, P. tabuliformis seedlings were irrigated daily with 2 M NaCl or 300 mM mannitol for 3 days; UV treatment raw data was from Xu J's study [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abiotic stresses have an extensive impact on various physiological, molecular, and metabolic responses. Much progress has been made in unravelling the complex stress response mechanisms, particularly in identifying stressresponsive genes with the help of biotechnological tools [1,2]. MicroRNAs (miRNAs), play a critical role in post-transcriptional regulation through base-pairing with other miRNA targets, including transcription factors (TFs) [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…Much progress has been made in unravelling the complex stress response mechanisms, particularly in identifying stressresponsive genes with the help of biotechnological tools [1,2]. MicroRNAs (miRNAs), play a critical role in post-transcriptional regulation through base-pairing with other miRNA targets, including transcription factors (TFs) [1,3]. Understanding the role of miRNAs in abiotic stresses may be helpful in the development of innovative ways for improving plant responses against abiotic stresses.…”
Section: Introductionmentioning
confidence: 99%